2016
DOI: 10.1038/ncomms13787
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin-remodelling factor Brg1 regulates myocardial proliferation and regeneration in zebrafish

Abstract: The zebrafish possesses a remarkable capacity of adult heart regeneration, but the underlying mechanisms are not well understood. Here we report that chromatin remodelling factor Brg1 is essential for adult heart regeneration. Brg1 mRNA and protein are induced during heart regeneration. Transgenic over-expression of dominant-negative Xenopus Brg1 inhibits the formation of BrdU+/Mef2C+ and Tg(gata4:EGFP) cardiomyocytes, leading to severe cardiac fibrosis and compromised myocardial regeneration. RNA-seq and RNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 69 publications
1
65
0
Order By: Relevance
“…However, in adults, Brg1 is turned off in cardiomyocytes and it is reactivated by cardiac stresses, and preventing Brg1 re-expression decreases hypertrophy [31]. Zebrafish experiment also showed that Brg1 promotes heart regeneration by repressing cyclin-dependent kinase inhibitors partly through Dnmt3ab-dependent DNA methylation [30]. Results herein showed that Brg1 was positively regulated by miR-99a in H9C2 cells, and overexpression of Brg1 attenuated hypoxiainduced cell injuries.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, in adults, Brg1 is turned off in cardiomyocytes and it is reactivated by cardiac stresses, and preventing Brg1 re-expression decreases hypertrophy [31]. Zebrafish experiment also showed that Brg1 promotes heart regeneration by repressing cyclin-dependent kinase inhibitors partly through Dnmt3ab-dependent DNA methylation [30]. Results herein showed that Brg1 was positively regulated by miR-99a in H9C2 cells, and overexpression of Brg1 attenuated hypoxiainduced cell injuries.…”
Section: Discussionmentioning
confidence: 61%
“…Brg1 is one of the central ATPase catalytic subunits, which is essential for zygote genome activation, erythropoiesis, cardiac development and neuronal development [30]. In embryos, Brg1 promotes cardiomyocyte proliferation by maintaining Bmp10 and suppressing p57 kip2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Brg1 expression is strongly induced upon injury in the wound edge, and overexpression of a dominant negative Brg1 blocks cardiomyocyte proliferation. The authors showed that Brg1 is required to prevent expression of cyclin‐dependent kinase inhibitors by increasing DNA methylation in collaboration with the methyltransferase Dnmt3ab (Xiao et al., ). It remains to be explored whether additional epigenetic mechanisms are involved in reactivating cardiomyocyte proliferation.…”
Section: Dynamics Of Zebrafish Heart Regenerationmentioning
confidence: 99%
“…The SWI/SNF chromatin‐remodeling factors Brg1 and Brm have been shown to regulate through altering the state of DNA methylation in a context‐dependent manner . DNA methylation is critical for efficient OPC expansion and early onset of differentiation, but not OPC survival , and is also important for efficient remyelination .…”
Section: Atp‐dependent Remodelers In Oligodendrocyte Specification Lmentioning
confidence: 99%